The Effect of Problem-based Learning through Blended Learning on Digital Literacy of Eleventh-Grade Students on Excretory System Material - Yustina, Y.; Mahadi, I.; Daryanes, F.; Alimin, E.; Nengsih, B. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
This study aims to analyze students’ digital literacy through problem-based Learning (PBL) through Blended Learning (BL). The research was carried out in the eleventh grade of SMA Negeri Plus Riau in the even semester of the 2021/2022 academic year. This research is quasi-experimental, using a closed questionnaire with 4 Linkert scales. The research parameter is students’ digital literacy with eight indicators: Functional Skills and Beyond, Creativity, Collaboration, Communication, The Ability to Find and Select Information, Critical Thinking and Evaluation, Cultural and Social Understanding, and E-Safety. Data were obtained using the Linkert scale and converted into Value (N). Value every aspect is the score obtained from the answer indicators that are checked (considered the most appropriate) and divided by the maximum score multiplied by 100. The average value of each aspect is obtained from the total value of each indicator divided by the number of indicators, then analyzed descriptively and qualitatively. Digital literacy students in the control class got an average score of 77.5 (good category) and 85.25 in the experimental class (very good category). Of the eight indicators, the highest digital literacy indicator in the control and experimental classes is creativity, with scores of 85 and 88, respectively. The E-Safety indicator scores 85 and 90. The lowest score was the Critical Thinking and Evaluation indicator, in the control and experimental classes, with a 75, categorized as good. Problem-based learning model through blended learning positively affects the digital literacy of eleventh-grade students of SMA Negeri Plus Riau on the excretory system material.